Multimodality Imaging of the Brain-Heart-Axis after Ischemic Stroke Reveals Acute and Chronic Cardiac Dysfunction after Cerebral Ischemia. (20th July 2021) - Hermanns, N; Bascunana, P; Polyak, A; Ross, T; Bengel, F; Thackeray, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): DFG; Ev Studienwerk Villigst Introduction: Cerebral ischemia remains a major contributor to global morbidity and mortality. Beyond neurological dysfunction, cerebral stroke also increases risk of subsequent cardiac events and development of chronic heart failure. The mechanisms underlying this brain-heart communication are poorly characterized, but systemic inflammation is thought to play a role. Purpose: We hypothesized that cerebral ischemic stroke evokes systemic inflammation contributing to acute cardiac stress and persistent contractile dysfunction, which may be monitored by serial molecular imaging by positron emission tomography (PET). Methods: C57Bl6 mice underwent transient (30min) intraluminal middle cerebral artery occlusion (MCAo, n = 88) to induce stroke or sham surgery (n = 18). Serial 18F-GE180 PET at 24h, 7d, and 21d after injury identified translocator protein (TSPO) in brain microglia and peripheral macrophages as a marker of inflammation. Magnetic resonance imaging (MRI) determined stroke size and characterized cardiac function at 1 and 3wk after MCAo. Imaging signals were confirmed by autoradiography, immunohistochemistry and fluorescence-activated cell sorting. Results:   MCAo in mice induced cerebral stroke of variable size (median 44.68mm3, range:5.12-139.60mm3). Localized inflammation in the injured hemisphere was observed by TSPO PET covering territory consistent to the stroke location, with marked increase in the neuroinflammatory signal at 7d relative to the contralateral hemisphere (% injected dose (ID)/g max: 3.82 ± 0.84 vs 2.51 ± 0.32, p < 0.001). TSPO signal was similarly elevated in the stroke region compared to sham animals (%ID/g max: 3.82 ± 0.84 vs 2.59 ± 0.72, p < 0.001). Corresponding with neuroinflammation, a heightened global myocardial TSPO signal was observed 7d after MCAo compared to sham (%ID/g: 7.75 ± 2.79 vs 5.61 ± 1.98, p = 0.041). TSPO PET signal remained elevated 21d after stroke in brain (3.20 ± 1.15 vs 2.46 ± 0.37, p = 0.012) and heart (8.62 ± 2.43 vs 5.85 ± 0.66, p = 0.022). Cerebral stroke was associated with reduced contractile function compared to sham at 1wk (ejection fraction, EF: 49.58 ± 16.90 vs 62.17 ± 5.25%, p = 0.025) and 3wk (54.30 ± 5.70 vs 66.06 ± 3.48%, p = 0.009). Larger stroke size identified early after injury by T2 weighted MRI, reflecting the focal injury and penumbra edema, correlated with worse subsequent cardiac function at 21d (r = 0.745, p = 0.009). Despite increased TSPO signal, flow cytometry showed comparable CD45+ leukocyte content in the left ventricle after MCAo compared to sham at 7d (p = 0.749). Conclusions: Ischemic stroke evoked parallel cerebral and cardiac TSPO upregulation and persistent contractile dysfunction, beginning early after injury. The extent and severity of brain injury predicts left ventricle dysfunction, but the role of inflammation requires further investigation. Molecular imaging may identify risk and guide novel therapies to improve cardiac outcome after stroke.